Unchanged cerebrovascular CO2 reactivity and hypercapnic ventilatory response during strict head‐down tilt bed rest in a mild hypercapnic environment. (2nd May 2020) - Laurie, Steven S.; Christian, Kate; Kysar, Jacob; Lee, Stuart M.C.; Lovering, Andrew T.; Macias, Brandon R.; Moestl, Stefan; Sies, Wolfram; Mulder, Edwin; Young, Millennia; Stenger, Michael B.
Abstract : Key points: Carbon dioxide levels are mildly elevated on the International Space Station and it is unknown whether this chronic exposure causes physiological changes to astronauts. We combined ∼4 mmHg ambient P C O 2 with the strict head‐down tilt bed rest model of spaceflight and this led to the development of optic disc oedema in one‐half of the subjects. We demonstrate no change in arterialized P C O 2, cerebrovascular reactivity to CO2 or the hypercapnic ventilatory response. Our data suggest that the mild hypercapnic environment does not contribute to the development of spaceflight associated neuro‐ocular syndrome. Abstract: Chronically elevated carbon dioxide (CO2 ) levels can occur in confined spaces such as the International Space Station. Using the spaceflight analogue 30 days of strict 6° head‐down tilt bed rest (HDTBR) in a mild hypercapnic environment ( P C O 2 = ∼4 mmHg), we investigated arterialized P C O 2, cerebrovascular reactivity and the hypercapnic ventilatory response in 11 healthy subjects (five females) before, on days 1, 9, 15 and 30 of bed rest (BR), and 6 and 13 days after HDTBR. During all HDTBR time points, arterialized P C O 2 was not significantly different from the pre‐HDTBR measured in the 6° HDT posture, with a mean (95% confidence interval) increase of 1.2 mmHg (–0.2 to 2.5 mmHg, P = 0.122) on day 30 of HDTBR. Respiratory acidosis was never detected, although a mild metabolic alkalosis developed on day 30 of HDTBR by a mean (95% confidence interval) pH change of 0.032 (0.022–0.043; P < 0.001), which remained elevated by 0.021 (0.011–0.031; P < 0.001) 6 days after HDTBR. Arterialized pH returned to pre‐HDTBR levels 13 days after BR with a change of –0.001 (–0.009 to 0.007; P = 0.991). Compared to pre‐HDTBR, cerebrovascular reactivity during and after HDTBR did not change. Baseline ventilation, ventilatory recruitment threshold and the slope of the ventilatory response were similar between pre‐HDTBR and all other time points. Taken together, these data suggest that the mildly increased ambient P C O 2 combined with 30 days of strict 6° HDTBR did not change arterialized P C O 2 levels. Therefore, the experimental conditions were not sufficient to elicit a detectable physiological response. Key points: Carbon dioxide levels are mildly elevated on the International Space Station and it is unknown whether this chronic exposure causes physiological changes to astronauts. We combined ∼4 mmHg ambient P C O 2 with the strict head‐down tilt bed rest model of spaceflight and this led to the development of optic disc oedema in one‐half of the subjects. We demonstrate no change in arterialized P C O 2, cerebrovascular reactivity to CO2 or the hypercapnic ventilatory response. Our data suggest that the mild hypercapnic environment does not contribute to the development of spaceflight associated neuro‐ocular syndrome.